2023
DOI: 10.1038/s41598-023-35939-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vmPFC-insula functional connectivity in generalized anxiety disorder: a Bayesian confirmation study

Abstract: Differences in the correlated activity of networked brain regions have been reported in individuals with generalized anxiety disorder (GAD) but an overreliance on null-hypothesis significance testing (NHST) limits the identification of disorder-relevant relationships. In this preregistered study, we applied both a Bayesian statistical framework and NHST to the analysis of resting-state fMRI scans from females with GAD and matched healthy comparison females. Eleven a-priori hypotheses about functional connectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Due to the restricted time of the COVID-19 pandemic and the recent time period involved in these studies, this was to be expected (i.e., recent studies are expected to be more methodologically sound). It should also be stressed that some of the alterations that we found to be shared among ptsD patients and survivors of COVID-19 infection (PFC, ACC, insula, and hippocampus) may also be found in patients with emotional disturbances, like anxiety and depressive disorders [81][82][83][84][85], and even in severe psychotic disorders, like schizophrenia [86]. With these disturbances and disorders all having a shared background with childhood trauma and adversity [87][88][89], it is almost impossible to disentangle what is specific to ptsD and COVID-19 and what could be nonspecific.…”
Section: Limitationsmentioning
confidence: 86%
“…Due to the restricted time of the COVID-19 pandemic and the recent time period involved in these studies, this was to be expected (i.e., recent studies are expected to be more methodologically sound). It should also be stressed that some of the alterations that we found to be shared among ptsD patients and survivors of COVID-19 infection (PFC, ACC, insula, and hippocampus) may also be found in patients with emotional disturbances, like anxiety and depressive disorders [81][82][83][84][85], and even in severe psychotic disorders, like schizophrenia [86]. With these disturbances and disorders all having a shared background with childhood trauma and adversity [87][88][89], it is almost impossible to disentangle what is specific to ptsD and COVID-19 and what could be nonspecific.…”
Section: Limitationsmentioning
confidence: 86%
“…Patients with GAD exhibited decreased microbial quantity and diversity, along with distinct metagenomic composition, suggesting microbiota dysbiosis in GAD patients (Jiang et al ., 2018 ). According to fMRI results, frontal lobe lesions causing a loss of functional connectivity between cortical areas such the insula, amygdala, anterior cingulate cortex, medial temporal, and prefrontal cortex (PFC) are characteristics of anxiety disorders (Fonzo, Etkin, 2017 ; Kenwood et al ., 2022 ; Steinhäuser et al ., 2023 ). Machine learning studies using fMRI as a feature have demonstrated the capacity to differentiate patients with anxiety disorders and healthy individuals within the controlled group.…”
Section: Exercise Influences Brain Healthmentioning
confidence: 99%